Convergence, context, crossvergence: contending perspectives on strategic management in Asia vs. the West. (27th March 2019) - Nathan, Maria L.
In what ways are the strategic management practices within Asia and the West similar and in what ways different? In search of an answer to this question, researchers have given shape to three perspectives: 1) universal convergence suggests that, for varied reasons, there is general practice among Asian and Western firms; 2) contextualism focuses upon cross-national firm difference; 3) crossvergence studies the synergistic effects of convergence and divergence among Asian and Western firms. Research findings to date depict complex, countervailing forces operating both within and outside firms, nations, and across the globe. It is argued that rejection of any one perspective is not appropriate at this time, and could deter progress toward a clearer understanding of difference, similarity, and cross-influence between and among Asian and Western firms. Recommendations for future research are offered, including alternative frameworks for reconciling the three perspectives.